Impact of endogenous melatonin on rhythmic behaviors, reproduction, and survival revealed in melatonin‐proficient C57BL/6J congenic mice. Issue 2 (24th June 2021) - Zhang, Chongyang; Clough, Shannon J.; Adamah‐Biassi, Ekue B.; Sveinsson, Michele H.; Hutchinson, Anthony J.; Miura, Ikuo; Furuse, Tamio; Wakana, Shigeharu; Matsumoto, Yui K.; Okanoya, Kazuo; Hudson, Randall L.; Kato, Tadafumi; et al.
Abstract: The hormone melatonin is synthesized from serotonin by two enzymatic reactions (AANAT and ASMT/HIOMT) in the pineal gland following a circadian rhythm with low levels during the day and high levels at night. The robust nightly peak of melatonin secretion is an output signal of the circadian clock to the whole organism. However, so far the regulatory roles of endogenous melatonin in mammalian biological rhythms and physiology processes are poorly understood. Here, we establish congenic mouse lines (>N10 generations) that are proficient or deficient in melatonin synthesis (AH+/+ or AH−/− mice, respectively) on the C57BL/6J genetic background by crossing melatonin‐proficient MSM/Ms with C57BL/6J. AH+/+ mice displayed robust nightly peak of melatonin secretion and had significantly higher levels of pineal and plasma melatonin vs AH−/− mice. Using this mice model, we investigated the role of endogenous melatonin in regulating multiple biological rhythms, physiological processes, and rhythmic behaviors. In the melatonin‐proficient (AH+/+) mice, the rate of re‐entrainment of wheel‐running activity was accelerated following a 6‐hour phase advance of dark onset when comparted with AH−/− mice, suggesting a role of endogenous melatonin in facilitating clock adjustment. Further in the AH+/+ mice, there was a significant decrease in body weight, gonadal weight and reproductive performance, and a significant increase in daily torpor (a hypothermic and hypometabolic state lasting only hours during adverse conditions). Endogenous melatonin, however, had no effect in the modulation of the diurnal rhythm of 2‐[ 125 I]‐iodomelatonin receptor expression in the SCN, free‐running wheel behavior in constant darkness, life span, spontaneous homecage behaviors, and various types of social‐emotional behaviors. The findings also shed light on the role of endogenous melatonin in mice domestication and provide new insights into melatonin's action in reducing energy expenditure during a food shortage. In summary, the congenic mice model generated in this study offers a significant advantage toward understanding of the role of endogenous melatonin in regulating melatonin receptor‐mediated rhythm behaviors and physiological functions.